Conscientious objections in medicine for abortions among the undergraduate medical students: a questionnaire-based survey - Dsouza, Oliver; Yalaburgi, Keerthi S. (International Journal Of Community Medicine And Public Health, 2022)
Background: Conscientious objection (CO) in medicine is less a focused area of research in India. Methods: In this questionnaire-based survey, responses from the students undergoing M.B.B.S./undergraduate training program from two medical colleges on voluntary abortion in general, and pertaining to the rape victims was obtained. We assessed the prevalence, influence of various factors and preference for referrals in CO towards abortion among the participants. Results: Of the 900 students approached, 765 (85.0%) (females 68%) completed and returned the questionnaire, of whom 63.5% had an urban background, 48.0% were Christians and 52.0% were non-Christians (Muslim-5.4%; Hindu-46.5%). Only 9.7% had CO (p=0.000). There was a greater acceptance to abortion irrespective of gender and area of residence, except for gestational age beyond 20 weeks. Non-Christians were likely to have no objections towards abortion (p<005). Christians did not have CO for congenital abnormalities in pregnancy <20 weeks (60%), raped minor, (<20 weeks, 74%; beyond 20 weeks, 61%). Among the students who had CO, irrespective of religion majority had no issues with referring the woman to another doctor. The only exception to this norm was among the non-Christian students, who in case of raped minor <20 weeks were more likely (60%) to not refer. Conclusions: CO is less prevalent among the Indian medical students and is towards voluntary termination of pregnancy, pregnancy beyond 20 weeks, when existed. Medical students were considerate towards rape victims. Religion plays a significant influential role in shaping the beliefs.